AKTUALISASI PRINSIP HUKUM PELESTARIAN FUNGSI LINGKUNGAN HIDUP DALAM KEBIJAKAN PERUBAHAN PERUNTUKAN, FUNGSI, DAN PENGGUNAAN KAWASAN HUTAN - Iskandar, Iskandar (Faculty of Law, Universitas Jenderal Soedirman, 2011)
This article are intended to describe the thirteen principles of environment conservation law in sustainable forest management as an instrument of prevention of forest damage. In the realization, almost all of the principles are not applied or not be the basis of consideration, either by the Ministry of Forestry, relevant sector ministries, and local governments in establishing the concervation policies. This makes the implementation of policies to use, changes in the function, and use (permission to borrow to use) the forest resist of violations and irregularities. Therefore, it needs to be developed (ius constituendum perspective) the principle of environmental law as a general principles, which has the nature of force and lead to the development of leadership character of the decision makers. Key words: Actualization, Principles of Law, Conservation, Environment Functions, Forest